Respuesta :

4x - 3y =   8  ⇒   8x - 6y = 16
5x - 2y = -11 ⇒ 15x - 6y = -33
                                 -7x = 49
                                  -7     -7
                                    x = -7
                           4x - 3y = 8
                       4(-7) - 3y = 8
                         -28 - 3y = 8
                       + 28      + 28
                               -3y = 36
                                -3     -3
                                  y = -12
                            (x, y) = (-7, -12)

To use elimination you have to multiply the first graph by 2 and the second graph by 3 so that the two y-axis can be equal to -6. Then you do the rest to find the answer of the x-axis and the y-axis.